Pertanggungjawaban Pihak Keluarga Terhadap Pelunasan Hutang Pihak yang Melarikan Diri Perspektif Wahbah Az-Zuhaili: Studi Kasus di Kelurahan Kota Pinang Kecamatan Kota Pinang Kabupaten Labuhanbatu Selatan - Husnul Akmal Marpaung; Abd. Rahman Harahap (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Hiwalah what happened in Penang City never informed the muhal alaihi about the debt to him so that it was always difficult for al muhal to collect his debt. In fact, not only that, the debt does not have proof of transaction at all, so it is difficult to transfer. This study aims to solve the problem of debt transfer without the consent of the alumni's muhal in Kota Pinang Village, Kota Pinang District, South Labuhanbatu Regency, the factors that make al muhal alaihi unwilling to pay the debt that has been transferred and the family's responsibility for the repayment of the debt of the fleeing party from the perspective of Wahbah Az-Zuhaili in Kota Pinang Village, Kota Pinang District, South Labuhanbatu Regency. This research uses empirical methods and the formulation of concepts and case approaches. The results of the study prove that Wahbah Zuhaili himself must be known to all parties so that when a default occurs, the muhal alaihi is ready to accept the consequences that occur. Not only that, Wahbah Zuhaili also considers that the deeds done by people who do hiwalah without the knowledge of muhal alaihi are considered invalid because one of the pillars is not fulfilled, namely the contract of muhal alaihi does not exist because of ignorance.